2015
DOI: 10.1002/hrm.21745
|View full text |Cite
|
Sign up to set email alerts
|

Entitlement to Work-Life Balance Support: Employee/Manager Perceptual Discrepancies and Their Effect on Outcomes

Abstract: We broaden contemporary understandings of the relationship between HR practices that support work‐life balance and organizational as well as individual outcomes, through a focus on perceptual discrepancies of entitlement. To theorize this notion, we adopt the self‐perception accuracy model and extend it by investigating whether any employee/management discrepancies in perceptions of entitlement mediate the relationship between HR practices supporting work‐life balance and outcomes. We use data from 20 European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Three studies used a single-item measure of conflict between the two domains. Goñi-Legaz and Ollo-López (2016) and Stavrou and Ierodiakonou (2016) used one item asking about worklife balance, whereas Fujimoto et al (2008) examined conflict in balancing work and child care.…”
Section: Measures Of Work-life Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies used a single-item measure of conflict between the two domains. Goñi-Legaz and Ollo-López (2016) and Stavrou and Ierodiakonou (2016) used one item asking about worklife balance, whereas Fujimoto et al (2008) examined conflict in balancing work and child care.…”
Section: Measures Of Work-life Interactionmentioning
confidence: 99%
“…Two studies examined the relationship between work-life interaction and both policy availability and use (O'Driscoll et al, 2003;Russell et al, 2009). Seven studies explored the relationship between policy use and worklife interaction, and in doing so, assessed availability of policies, but did not analyse outcomes in terms of policy availability (Aycan & Eskin, 2005;Fujimoto et al, 2008;Goñi-Legaz & Ollo-López, 2016;Jang et al, 2016;Secret & Sprang, 2002;Stavrou & Ierodiakonou, 2016;Thompson & Prottas, 2005). The remaining seven studies examined only the availability of policies, not use, in relation to work-life interaction (Afrianty et al, 2015;Breaugh & Frye, 2008;Brough et al, 2005;Hammer et al, 2005;Lapierre & Allen, 2006;Lembrechts et al, 2015;Somech & Drach-Zahavy, 2012).…”
Section: Policy Availability Versus Usementioning
confidence: 99%
See 1 more Smart Citation
“…A related argument is conveyed in the psychological contract theory, proposing that if employees feel entitled to FWAs or if such practices become a right built into the employee−employer psychological contract, then such practices might not be perceived as a benefit anymore (Putnam et al, ). Employees with a strong sense of entitlement are more likely to show low motivation and engagement and, therefore, are less likely to show reciprocity (Stavrou & Ierodiakonou, ). Consequently, any positive association between employee‐centered FWAs and work effort will weaken.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Flexible work practices should therefore enhance the likelihood of disclosure of caregiving responsibilities by positively shaping an employee's judgment of the ease of disclosure and its potential benefits and costs. For example, Stavrou and Ierodiakonou () found that the availability of work–life practices strengthened managers belief that the organizations had an ethical obligation to support employee work–life needs. This position is supported in the disability literature where researchers have observed that HR practices enhance the likelihood of disclosing a “hidden” identity to supervisors and coworkers (Santuzzi & Waltz, ).…”
Section: Theoretical Context and Hypothesesmentioning
confidence: 99%